(3GdchcH GdhbGO aj CMcGe GdELJgGOs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdMcje GdPi ChVM HfG efG GdNjQGJ , hLYd HCJHGYfG GdhUhd Edi CYdi GdOQLGJ s
(3BNQgG (B:s
(3hdbO HUQce Gddg ai ehGWf cKjQI hdG GdESJYGfI EdG Hg , hdG GdJhajb EdG SfI hdG GdEYJeGO EdG Ydjg , hgh MSHfG hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hgh LhGH Yf SDGd ef Gdabjg HOQ GdOjf eMeO Hf eQRhb s
(3HBNQgG SeGY hebGHdI s
(3cJHJ GdYfGhjjf HGdMeQI s
(3JHUQGJ GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis